Language Development or Language Corruption? The Case of Loan-words in Isichazamazwi SesiNdebele - Ncube, Cornelias (Lexikos, 2005)
ABSTRACT: This article discusses the loan-words in Isichazamazwi SesiNdebele (henceforth ISN), particularly looking at their acceptance and/or non-acceptance by the target users of ISN. In Zim-babwe, Ndebele shares the same linguistic environment with English, Shona and the official mi-nority languages such as Kalanga, Tonga and Nambya. A historical heritage also links it with its Nguni sister languages such as Zulu and Xhosa spoken in South Africa. In selecting headwords for ISN, the Ndebele Lexicographic Unit used the frequency-list method, lemmatising words mostly found in the corpus. This method inevitably allowed the adoption of loan-words in the ISN with resultant public protest. The article is divided into two broad sections. The first section gives a gen-eral overview of comments from users of ISN about the inclusion of loan-words in the dictionary. The attitude towards loan-words in the ISN varies with different age groups, the younger gen-eration freely accepting them as part of the Ndebele lexicon as opposed to the older generation. The second section analyses the justification by the editors of ISN for lemmatising loan-words against the views of target users. Reservations against the loan-words in ISN go beyond lexicographic prin-ciples. In the forefront is the users' attitude towards the source language. Language attitudes in Zimbabwe are mainly a result of the socio-political and economic power characterising the differ-ent tribal or ethnic groups in the country. The article concludes by discussing possible solutions to the problem of loan-words to be adopted in the forthcoming Advanced Ndebele Dictionary.Keywords: LOAN-WORDS, CULTURAL BORROWING, DIALECT BORROWING, LEXI-CON, ADOPTION, LANGUAGE PURISM, LANGUAGE EMANCIPATION*****OPSOMMING: Taalontwikkeling of taalbederf? Die geval van leenwoorde in Isichazamazwi SesiNdebele. Hierdie artikel bespreek die leenwoorde in Isichazamazwi SesiNdebele (voortaan ISN) deur veral te kyk na hul aanvaarding en/of nieaanvaarding deur die teikengebruikers van ISN. In Zimbabwe deel Ndebele dieselfde taalomgewing met Engels, Sjona en die offisiële minderheidstale soos Kalanga, Tonga en Nambya. 'n Historiese erfenis verbind dit ook met die Ngunisustertale soos Zoeloe en Xhosa wat in Suid-Afrika gepraat word. Vir die keuse van trefwoorde in ISN, het die Ndebele- leksikografiese eenheid die frekwensielysmetode gebruik deur die woorde te lemmatiseer wat die meeste in die korpus aangetref is. Hierdie metode het onvermydelik die opname van leenwoorde in die ISN toegelaat met die gevolglike openbare protes. Die artikel is in twee breë afdelings verdeel. Die eerste afdeling gee 'n algemene oorsig van die kom-mentaar van die gebruikers van ISN op die insluiting van leenwoorde in die woordeboek. Die houding teenoor leenwoorde in die ISN wissel by verskillende ouderdomsgroepe, met die jonger geslag wat hulle vrylik as deel van die Ndebeleleksikon aanvaar in teenstelling tot die ouer geslag. Die tweede afdeling ontleed die regverdiging deur die redakteurs van ISN vir die lemmatisering van leenwoorde teenoor die beskouings van die teikengebruikers. Voorbehoude teen die leenwoor-de in ISN gaan verder as leksikografiese beginsels. Vooraan is die gebruikers se houding teenoor die brontaal. Taalhoudings in Zimbabwe is hoofsaaklik die gevolg van die sosiopolitieke en eko-nomiese sterkte wat die verskillende stam- of etniese groepe in die land kenmerk. Die artikel sluit af met 'n bespreking van moontlike oplossings vir die probleem van leenwoorde wat in die toe-komstige Gevorderde Ndebelewoordeboek opgeneem sal word.Sleutelwoorde: LEENWOORDE, KULTURELE ONTLENING, DIALEKONTLENING, LEK-SIKON, OORNAME, TAALPURISME, TAALEMANSIPASIE